Spectroscopic properties, anti-colon cancer, antimicrobial and molecular docking studies of silver(I), manganese(II), cobalt(II) and nickel(II) complexes for 2-amino-4-phenylthiazole derivative - Al-Harbi, Sami Abdullah; Bashandy, Mahmoud Sayed; Al-Saidi, Hammed Mohammed; Emara, Adel Abbas Ahmed; El-Gilil, Shimaa Mohamed Abd (European Journal of Chemistry, 2016)
Thiazole Schiff base (H2L) ligand was synthesized from condensation of 2-amino-4-phenylthiazole with 4,6-diacetylresorcinol in the molar ratio 2:1. A series of Ag(I), Mn(II), Co(II) and Ni(II) complexes of H2L ligand was prepared and investigated by elemental analysis, IR, UV, 1H NMR, TGA and mass spectral data. Thiazol Schiff base ligand has two bidentate sets of N-O units which can coordinate with two metal ions to afford novel binuclear metal complexes. The directions of the coordinate bonds are from nitrogen atoms of the azomethine groups and oxygen atoms of the phenolic groups. All of the newly synthesized complexes were evaluated for their antimicrobial activities. The results showed the Ag(I) complex exhibited better activities than the commercial antimicrobial reference drugs. The metal complexes were also evaluated for their in-vitro anti-colon human cancer (HCT-116) and mammalian cells of the African green monkey kidney (VERO). The Ag(I) and Co(II) complexes with selectivity index value 17.00 and 15.63, respectively, exhibited better activity than methotrexate as a reference drug with selectivity index value 13.30, while complexes Ni(II) and Mn(II) with selectivity index values 9.30 and 8.59, respectively, were found to be nearly as active as methotrexate. Molecular docking studies further helped in understanding the mode of action of the compounds through their various interactions with the active sites of the dihydrofolate reductase enzyme. The observed activity of the Ag(I), Mn(II) and Ni(II) complexes gave rise to the conclusion that they might exert their action through inhibition of the dihydrofolate reductase enzyme.